2018
DOI: 10.3389/fcimb.2018.00130
|View full text |Cite
|
Sign up to set email alerts
|

FcpB Is a Surface Filament Protein of the Endoflagellum Required for the Motility of the Spirochete Leptospira

Abstract: The spirochete endoflagellum is a unique motility apparatus among bacteria. Despite its critical importance for pathogenesis, the full composition of the flagellum remains to be determined. We have recently reported that FcpA is a novel flagellar protein and a major component of the sheath of the filament of the spirochete Leptospira. By screening a library of random transposon mutants in the spirochete Leptospira biflexa, we found a motility-deficient mutant harboring a disruption in a hypothetical gene of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…5A-C). This observation supports and extends previous reports associating these 227 mutations with loss of filament curvature together with pronounced functional effects (Wunder, 228 Figueira, Benaroudj, et al, 2016;Wunder et al, 2018). Wild-type filament segments exhibit a single 229 peak in the measured curvature distribution (Fig.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…5A-C). This observation supports and extends previous reports associating these 227 mutations with loss of filament curvature together with pronounced functional effects (Wunder, 228 Figueira, Benaroudj, et al, 2016;Wunder et al, 2018). Wild-type filament segments exhibit a single 229 peak in the measured curvature distribution (Fig.…”
supporting
confidence: 88%
“…The asymmetric localization of FcpA and FcpB, specifically on the convex side of the sheath, is 154 distinct from previously characterized exoflagella but is consistent with prior flagellum electron-155 microscopic imaging studies performed with antibody labels (Wunder, Figueira, Benaroudj, et al, 156 2016;Wunder et al, 2018). The localization of FcpB sites were further validated by comparison 157 with a similar reconstruction of filaments from an fcpBmutant ( Fig.…”
supporting
confidence: 79%
“…As seen in other spirochetes, the leptospiral genomes exhibit an atypically high number of structural flagellar genes, including four FlaB subunits with homology to FliC, the unique flagellin monomer forming the filament of Salmonella spp. The structure of the leptospiral filament and the roles of the different flagellar proteins and additional specific components of leptospires, such as the Fcp proteins (3)(4)(5)(6)(7), have been recently elucidated by highresolution cryo-electron microscopy coupled to model building and crystallography analyses (8). These studies revealed that the leptospiral filament has an atypical flattened helical shape, and that the four FlaB subunits constitute the core of the flagellum, surrounded by two FlaA and two Fcp subunits forming a sheath (8).…”
Section: Introductionmentioning
confidence: 99%
“…Another important role of the PF is to establish a wavy morphology, similar to a cytoskeleton, and the PF dependence of spirochete morphology has been observed in the periodontal disease-associated spirochetes Treponema denticola [25], B. burgdorferi [26,27], and Leptospira spp. [15,[19][20][21][22]. For example, the loss of the PF in B. burgdorferi straightens the entire cell body [26].…”
Section: Physical Properties Of the Pf Filamentmentioning
confidence: 99%
“…These results suggest that FcpA is a major sheath component and plays a central role in coiling via its interaction with the core filament. Recently, cryo-electron microscopy revealed that FcpB is a sheath protein that is localized along the outer curve of the PF, suggesting a contribution to PF coiling [22,23].…”
Section: Structure Of the Pf Filamentmentioning
confidence: 99%